Non-collinear magnetism and topological electronic structure in the half-Heusler compounds PrNiBi and PrPtBi - Leila Mikaeilzadeh; Farhad Khoeini; Ali Tavana (Scientific Reports)
Abstract Magnetism plays a crucial role in advanced technologies and fundamental materials science. Among various magnetic materials, compounds incorporating rare earth elements with non-collinear magnetic orders have garnered significant attention. In this study, we investigate different magnetic orders in Pr(Ni, Pt)Bi compounds using density functional theory (DFT), incorporating the Hubbard on-site interaction for the Pr atom. The results indicate that the antiferromagnetic (AFM) order is the most stable phase in these compounds, with an energy several meV lower than the considered non-collinear orders. Furthermore, band inversion, a characteristic feature of topological properties, is observed in both cases. We also assess the distance-dependent exchange interactions within these structures. The findings have significant implications for the development of advanced spintronic devices, magnetic sensors, and novel magnetic materials with topological properties, paving the way for innovative applications in modern technology.